Guanosine Nucleolipids: Synthesis, Characterization, Aggregation and X‐Ray Crystallographic Identification of Electricity‐Conducting G‐Ribbons. Issue 5 (15th May 2019) - Reuter, Hans; van Bodegraven, Anna Maria; Bender, Eugenia; Knies, Christine; Diek, Nadine; Beginn, Uwe; Hammerbacher, Katharina; Schneider, Vanessa; Kinscherf, Ralf; Bonaterra, Gabriel A.; Svajda, Rainer; Rosemeyer, Helmut
Abstract: The lipophilization of β ‐d ‐riboguanosine (1 ) with various symmetric as well as asymmetric ketones is described (→3a –3f ). The formation of the corresponding O ‐2′, 3′‐ketals is accompanied by the appearance of various fluorescent by‐products which were isolated chromatographically as mixtures and tentatively analyzed by ESI‐MS spectrometry. The mainly formed guanosine nucleolipids were isolated and characterized by elemental analyses, 1 H‐, 13 C‐NMR and UV spectroscopy. For a drug profiling, static topological polar surface areas as well as 10 log P OW values were calculated by an increment‐based method as well as experimentally for the systems 1‐octanol‐H2 O and cyclohexane‐H2 O. The guanosine‐ O ‐2′, 3′‐ketal derivatives 3b and 3a could be crystallized in (D6 )DMSO – the latter after one year of standing at ambient temperature. X‐ray analysis revealed the formation of self‐assembled ribbons consisting of two structurally similar 3b nucleolipid conformers as well as integrated (D6 )DMSO molecules. In the case of 3a  ⋅ DMSO, the ribbon is formed by a single type of guanosine nucleolipid molecules. The crystalline material 3b  ⋅ DMSO was further analyzed by differential scanning calorimetry (DSC) and temperature‐dependent polarization microscopy. Crystallization was also performed on interdigitated electrodes (Au, distance, 5 μm) and visualized by scanning electron microscopy. Resistance and amperage measurements clearly demonstrate that the electrode‐bridging 3b crystals are electrically conducting. All O ‐2′, 3′‐guanosine ketals were tested on their cytostatic/cytotoxic activity towards phorbol 12‐myristate 13‐acetate (PMA)‐differentiated human THP‐1 macrophages as well as against human astrocytoma/oligodendroglioma GOS‐3 cells and against rat malignant neuroectodermal BT4Ca cells. Abstract :